Ternary molybdenum disulfide nanosheets-cobalt oxide nanocubes-platinum composite as efficient electrocatalyst for hydrogen evolution reaction - Zainal, Siti Nuraqidah; Sookhakian, Mehran; Woi, Pei Meng; Alias, Yatimah (Elsevier, 2020)
A high-performance ternary composite electrocatalyst, consisting of a molybdenum disulfide-cobalt oxide-platinum (Mo–Co–Pt) composite is synthesized by facile hydrothermal methods and then used as an electrocatalyst for hydrogen evolution reaction (HER). The ternary composite of Mo–Co–Pt is characterized using transmission electron microscopy, X-ray photoelectron spectroscopy, Raman spectroscopy, and linear sweep voltammetry. The as-synthesized Mo–Co–Pt-modified glassy carbon electrode shows better electrocatalytic performance than that of pure molybdenum disulfide (MoS2) nanosheets and cobalt oxide (Co3O4) nanocubes. Besides, the ternary composite electrode exhibits Pt-like performance along with the smallest Tafel slope and superior electrocatalytic stability in an acidic medium. Based on BET specific surface area and electrochemical impedance spectroscopy measurements, the MoS2 nanosheets and Pt nanoparticles enhance HER activity of the Co3O4 nanocubes in the ternary composite due to the synergistic effect between the two-dimensional structure and large surface area of MoS2 nanosheets and excellent electrocatalytic activity of the Pt nanoparticles. © 2020 Elsevier Ltd